The Influence of Macro Role Playing Methods on Children's self help Skills of Group B - Prasetya, Bernadeta Chika; Kurniawati, Asih Budi; Pradini, Susanthi (PIAUD Universitas Islam Negeri Sunan Kudus, 2022)
The problem in this study was not yet skilled in helping themselves such as not bringing their own things at school, and there are still some children who cannot wear their own clothes and are accustomed to being accompanied, assisted, and also served. The purpose of this study was to determine the effect of the macro role-playing method on the self-help skills of group B children in Amarta Tani Kindergarten, HKTI. The type of this research approach is quantitative with the type of experimental research. The research design used in this study is a Quasi Experimental design using non-random re-experimentation (non-randomized pre-test posttest control group design). The data collection technique used is observation. The data analysis technique used in this study is a statistical analysis of the T-Test with the Independent-Sample T-Test. The results showed that there was a difference in values between the post-test experimental class and the pre-test control class, namely 49.39 and 40.30 with a significance value of 0.000 which means <0.05, then Ho is rejected and Ha is accepted.